The Role of Intellectual Capital in Moderating the Effect of Operating Cash Ratio and Leverage on Financial Distress - Ratieh Widhiastuti; Aulia Istna Karimah (Journal of Applied Accounting and Taxation, 2024)
This study aims to analyze the direct and indirect effects of the operating cash ratio and leverage on financial distress with intellectual capital as a moderating variable. This study uses 240 analysis units from 48 property and real estate companies listed on the Indonesia Stock Exchange for 2018-2022. Data analysis uses descriptive statistical analysis and moderated regression analysis. The results of the study show that the operating cash ratio has a negative effect on financial distress. Leverage proxied by DAR has a positive impact on financial distress. Intellectual capital cannot moderate the negative effect of the operating cash ratio on financial distress but can weaken the positive impact of leverage on financial distress. This study provides implications for company management to pay attention to the management of the operating cash ratio and leverage, as well as ensuring that the utilization of intellectual capital functions optimally to reduce the risk of financial distress.